2017
DOI: 10.1016/j.neuron.2017.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Motor Cortical Visuomotor Feedback Activity Is Initially Isolated from Downstream Targets in Output-Null Neural State Space Dimensions

Abstract: Summary Neural circuits must transform new inputs into outputs without prematurely affecting downstream circuits, while still maintaining other ongoing communication with these targets. We investigated how this isolation is achieved in motor cortex when macaques received visual feedback signaling a movement perturbation. To overcome limitations in estimating the mapping from cortex to arm movements, we also conducted brain-machine interface (BMI) experiments where we could definitively identify neural firing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
88
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 65 publications
(98 reference statements)
8
88
1
Order By: Relevance
“…However, this interpretation has several limitations or other possible explanations: positional effects could be small within the limited range of positions sampled during the Radial 8 Target Task; position-related modulation could be outside the two neural dimensions that affect the decoder 26,27 ; and/or position-related neural modulation could be poorly described by a linear fit. To more thoroughly investigate cursor positional effects without these limitations, we performed a set of experiments where monkeys performed a Random Target Task in which longer target hold epochs occurred across a larger span of the workspace.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this interpretation has several limitations or other possible explanations: positional effects could be small within the limited range of positions sampled during the Radial 8 Target Task; position-related modulation could be outside the two neural dimensions that affect the decoder 26,27 ; and/or position-related neural modulation could be poorly described by a linear fit. To more thoroughly investigate cursor positional effects without these limitations, we performed a set of experiments where monkeys performed a Random Target Task in which longer target hold epochs occurred across a larger span of the workspace.…”
Section: Resultsmentioning
confidence: 99%
“…A more engineering-minded reason for examining hold epoch data is these are used to fit the Cursor Position Subtraction model of the ReFIT decoder, and one goal of this study was to verify whether this decoder operation was useful in the absence of overt arm movements. Nonetheless, we wanted to also compare movement-epoch positional effects between arm and BMI use, especially in light of evidence that the motor system operates in different regimes between moving and holding-in-place during both arm 11,2830 and BMI use 27 .…”
Section: Resultsmentioning
confidence: 99%
“…This is possible if aspects of neural activity occupy a ‘null-space’: dimensions that do not directly contribute to the outgoing command 60,63,64 . The example in Fig 7A contains a simple one-dimensional null space.…”
Section: Resultsmentioning
confidence: 99%
“…However, neural activity outside this subspace, i.e. in the decoder-null space, will have no direct effect on kinematics [73]. The steady state equation can also be written as: vt=trueτ=0tM1tτM2yt, which shows that the current velocity is a causal smoothing of the neural push.…”
Section: Methodsmentioning
confidence: 99%
“…Additional motivating evidence comes from an intracerebral study which found that supplementary motor area (SMA) is modulated by a response task outcome [21] making it a prime candidate for electrode targeting in the future. Other intracortical recording studies found evidence for execution error modulation in M1 and premotor cortex [72,73]. Nonetheless, it is not yet clear whether outcome error signals are present in M1 and PMd, which motivates an intracortical investigation.…”
mentioning
confidence: 96%